2016
DOI: 10.18632/oncotarget.7415
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GADS enhances FLT3-induced mitogenic signaling

Abstract: GADS is a member of a family of SH2 and SH3 domain-containing adaptors that functions in tyrosine kinase-mediated signaling cascades. Its expression is largely restricted to hematopoietic tissues and cell lines. Therefore, GADS is mainly involved in leukocyte-specific protein tyrosine kinase signaling. GADS is known to interact with tyrosine-phosphorylated SHC, BCR-ABL and KIT. The SH2 domain of GADS has a similar binding specificity to that of GRB2 but its SH3 domain displays a different binding specificity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…4a) raised the possibility that the resistant cells carry an oncogenic internal tandem duplication (ITD) mutation in FLT3, which typically gives this pattern of expression. 15,16 This is also supported by the fact that resistant RS4;11 cells showed constitutive tyrosine phosphorylation of FLT3 as well as constitutive STAT5 phosphorylation (Fig. 4b) and that the second-generation FLT3 inhibitor AC220 could block tyrosine phosphorylation of both FLT3 and STAT5 (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…4a) raised the possibility that the resistant cells carry an oncogenic internal tandem duplication (ITD) mutation in FLT3, which typically gives this pattern of expression. 15,16 This is also supported by the fact that resistant RS4;11 cells showed constitutive tyrosine phosphorylation of FLT3 as well as constitutive STAT5 phosphorylation (Fig. 4b) and that the second-generation FLT3 inhibitor AC220 could block tyrosine phosphorylation of both FLT3 and STAT5 (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…18 Similarly, our results relevant to FLT3 mutant receptor show that R972/R973 methylation maintains phosphorylation of the nearby Y969 residue, a docking site for the SH2 domain containing proteins like Grb2 and GADS, which activates downstream pathways, including STAT5 and AKT. 19,30 Interestingly, our results indicate that R972/973 methylation enhances Y969 phosphorylation-initiated binding of the SH2 domain with FLT3 peptide. Thus, the effects of R972/973 methylation in promoting phospho-STAT5 and phospho-AKT levels are partially due to Y969 phosphorylation.…”
Section: Discussionmentioning
confidence: 59%
“…FLT3 phospho-Y969 reportedly acts as a docking site for the SH2 domains of cytosolic signaling molecules. 19 Thus, to evaluate whether methylated R972/973 functions to recruit other factors containing an SH2 domain to phospho-Y969, we performed molecular dynamics simulations of a phospho-FLT3 C-terminal (aa 969-974) peptide pYQNRRP in complex with the SH2 domain. Our simulated binding pose of the FLT3 peptide was in excellent agreement with the binding pose of the peptide in the crystal structure ( Figure 4C).…”
Section: Prmt1 Regulates Aml Cells Through Catalyzing Flt3-itd R972/9mentioning
confidence: 99%
“…FLT3 pY969 reportedly serves as a docking site for SH2 domains of cytosolic signaling molecules such as GADS and GRB2. 28,29 Thus we performed peptide pull-down assays to assess whether R972/973me2a enhanced the association between SH2 domain and FLT3 pY969. We found that purified GST-GRB2 SH2 domain bound pY969 peptide, as expected, 29 and greater amounts of GST-GRB2 protein were pulled down by pY969-R972/973me2a (Y phosphorylation plus R methylation) double-modified peptide ( Figure 3D).…”
Section: Prmt1-mediated R972/973 Methylation Regulates Leukemia Cell mentioning
confidence: 99%